Efficiency analysis of helium-cooled MAS DNP: case studies of surface-modified nanoparticles and homogeneous small-molecule solutions. Issue 8 (23rd February 2021) - Matsuki, Yoh; Kobayashi, Takeshi; Fukazawa, Jun; Perras, Frédéric A.; Pruski, Marek; Fujiwara, Toshimichi
Abstract : DNP enhancement, paramagnet-induced quenching/depolarization and build-up times are studied in a heterogeneous catalyst between 30 and 100 K. He-cooled MAS DNP at 30 K provides up to 100-fold better time performance than N2 -cooled MAS DNP at 90 K. Abstract : Despite the growing number of successful applications of dynamic nuclear polarization (DNP)-enhanced magic-angle spinning (MAS) NMR in structural biology and materials science, the nuclear polarizations achieved by current MAS DNP instrumentation are still considerably lower than the theoretical maximum. The method could be significantly strengthened if experiments were performed at temperatures much lower than those currently widely used (∼100 K). Recently, the prospects of helium (He)-cooled MAS DNP have been increased with the instrumental developments in MAS technology that uses cold helium gas for sample cooling. Despite the additional gains in sensitivity that have been observed with He-cooled MAS DNP, the performance of the technique has not been evaluated in the case of surfaces and interfaces that benefit the most from DNP. Herein, we studied the efficiency of DNP at temperatures between ∼30 K and ∼100 K for organically functionalized silica material and a homogeneous solution of small organic molecules at a magnetic field B 0 = 16.4 T. We recorded the changes in signal enhancement, paramagnet-induced quenching and depolarization effects, DNP build-up rate, and Boltzmann polarization. For these samples, the increases in MAS-induced depolarization and DNP build-up times at around 30 K were not as severe as anticipated. In the case of the surface species, we determined that MAS DNP at 30 K provided ∼10 times higher sensitivity than MAS DNP at 90 K, which corresponds to the acceleration of experiments by multiplicative factors of up to 100.